The Role of School Principals as Mobilizing Teachers in the Implementation of The Independent Curriculum at Senior High School Level in Selayar Islands District - Asmilasari Asmilasari; Hartini Hartini; Erni Rismawanti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims 1). To find out the role of the driving teacher as the principal in implementing the independent curriculum in the SMA / SMK level education unit in the Selayar Islands Regency 2). To find out the principal's leadership of the driving teacher in implementing the independent curriculum at the SMA / SMK level education unit in the Selayar Islands Regency 3). To find out the challenges of the driving teacher with his leadership competence in implementing the independent curriculum in the SMA / SMK level education unit in the Selayar Islands district. This research is a qualitative study using a phenomenological approach. The research was conducted on SMA/SMK principals who came from motivating teachers in Selayar Islands Regency consisting of SMAN 5 Selayar, SMAN 6 Selayar, SMKN 7 Selayar. SMKN 8 Selayar and the informants were the principals. The data collection techniques are observation, interviews and questionnaires, documentation, and data validity. Data analysis techniques with data collection, data reduction, data presentation and verification. The results showed that 1). The driving teacher as a school principal has several roles, namely as a manager, motivator, innovator, collaborator and leader in implementing the Merdeka Curriculum 2). The Principal's leadership of the driving teacher in implementing the Merdeka Curriculum at SMA / SMK is a leader who is able to drive learning, and ensure the implementation of IKM runs well 3). The challenges of the driving teacher in his leadership competence in implementing the independent curriculum are the lack of understanding of fellow teachers about IKM, the difficulty of fellow teachers making changes, and the understanding that the driving teacher has perfect abilities compared to other teachers.